SPECT-CT in Radiotherapy Planning, with Main Reference to Patients with Breast Cancer - Sergieva, Sonya; Mihaylova, Iglika; Alexandrova, Elena; Dimcheva, Milena; Mansi, Luigi (Current Radiopharmaceuticals, 2015)
The aim of modern intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) is to define the target areas including the smallest non-invaded margins, thus reducing the radiation dose to radiosensitive organs. To reach this goal, these methods require a more precise target delineation by imaging to better define the viable part of the tumor. Image-guided selection and demarcation of Gross Tumor Volume (GTV), Clinical Target Volume (CTV) and Organs at Risk (OAR) are the main steps to reach a satisfactory radiation treatment plan. Hybrid machines, such as PET-CT, SPECT-CT and, more recently, PET-MRI, may significantly increase diagnostic accuracy improving either sensitivity and specificity achievable alone by the single constituents of the hybrid tools. While the implementation contribution of PET-CT in radiotherapy, with respect to CT stand alone, has been extensively and successfully investigated, few papers have been at present written on the possible role of SPECT-CT for the same purpose. With an identical contribution to CT, SPECT may give similar information with respect to PET, when suitable radiopharmaceuticals are available. In particular, SPECT may provide additional information to CT, better defining the viable tumor mass; as a consequence, a more effective delineation of the GTV, saving the maximum normal tissue as possible, may be allowed. In this paper, we review some of the most important applications of SPECT-CT in oncology, as a premise to its possible utilization in tumor target definition in radiotherapy. In particular, we discuss sentinel lymph node (SLN) detection, tumor imaging with cationic lipophilic radiotracers, as 99mTc-methoxyisobutylisonitrile (MIBI) and 99mTc-tetrofosmin (TF) in breast cancer, thymoma, and lung cancer, 99mTcmethylene diphosphonate (MDP) for bone scan, 131Iodine and 123Iodine in differentiated thyroid cancer (DTC), as useful methods to optimize GTV and CTV definition. A reflection on the possible role in radiotherapy of other radiotracers labeled with gamma emitters, such as In-111 pentreotide has also been included.
Keywords: sentinel node